THE IMPACT OF MAIN TILLAGE SYSTEMS AND TYPICAL BLACK SOIL FERTILISATION ON THE LUMBRICIDES POPULATION IN A PLOW LAYER OF SOIL AND ON THE PRODUCTIVITY OF SHORT CROP ROTATION - Примак, І. Д.; Панченко, І. А.; Панченко, О. Б.; Левандовська, С. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The study is devoted to the analysis of the influence of four primary processing and fertilizer systems on the change in the number of lumbricides in the arable layer of typical black soil and the productivity of field grain-sowing crop rotation. The study material was the amount of lumbricides in the arable layer of black soil and their distribution depending on the main processing and fertilizer systems. The research methodology is based on experimental data obtained during 2016-2018 with a two-factor stationary field experiment, established in 2006 on the experimental field of the Belotserkovsky NAU. The highest amount of lumbricides in soil layers of 0-10, 20-30 and 0-30 cm is established under differential tillage, that is correspondently 39,3, 5,3 and 61,9 examples per square meter. It is 27,2, 20,5 and 24,0 percent more than on the watch list. Under poweredless and disc tillage there were correspondently 61,1 and 60,0 examples of lumbricides per square meter in a plow layer, so the results were close to powered-powerdless tillage. The decrease of the lumbricides population is observed during a crop vegetation. The biggest decrease in their number in a plow layer is established under powered tillage, that is 58,0%, and the smallest decrease is observed under poweredless tillage – 54,4 %. Under a disc and differential tillage such decrease was correspondently 55,0 and 56,0 %. The exact principles of lumbricides distribution in different parts of a plow layer under different main tillage systems are not established. Only a small increase in their number could be seen in a soil layer of 0-10 cm under poweredless and differential tillage and a decrease was observed under a disc tillage in comparison with the powered one. Thus, from the general number in a plow layer the amount of lumbricides in soil layers of 0-10, 10-20 and 20-30 cm was correspondently: under a powered tillage – 61,9; 29,3 and 8,8%, a poweredless tillage – 63,0; 29,6 and 7,4 %, a powered-poweredless tillage - 63,5; 28,1 and 8,4 %, a disc tillage – 60,0; 31,8 and 8,2 %. After the first, the second and the third levels of fertilization the number of lumbricides population was increasing correspondently 1,56, 2,07 and 2,32 times in comparison with the unfertilized areas. The productivity of a crop rotation does not differ significantly under a powered and a powered-poweredless tillage, but under a disc and poweredless ones it is much lower